A Pragmatic Analysis of Arabic Proverbs with Reference to their Equivalence and Non-Equivalence in English - Abdulrazaq, Muhammad F. (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2022)
Proverbs can be defined as culture-laden expressions used for transferring wisdom, recommendations, warning, giving a piece of advice…etc. Theoretically, they are treated as something that should always be replaced by equivalent in the target language. They are also required to be clarified and justified in the source before the target culture since many of them cannot be easily understood. Thus, the translator seeks to find an equivalent of the proverb in the target language. If he does not find a translation of the meaning behind these words, he would delete the proverb altogether or translating them by word-for-word translation. This may be the best way to translate instead of confusing the reader with words that he does not understand its cultural connotations. Proverbs can close the door that may lead the readership to the customs, morals, ideas and even the myths of these cultures that s/he reads about. In this paper, the researcher tackled some Iraqi Arabic famous proverbs to be pragmatically analyzed to show their meaning with reference to their equivalents in the target language. It has been shown that the Iraqi proverbs involve a speech act of warning, advice, irony, etc.
Keywords: الأمثال الشعبية -- علم الترجمة -- اللغة الإنجليزية